The Electrospinnability of Visco-Elastic Sugar Solutions - Lepe Pablo G. T.; Tucker Nick; Watson Andrew J.A.; LeCorre-Bordes Deborah; Fairbanks Antony J.; Staiger Mark P. (Applied Rheology, 2017)
It has been proposed that hydrogen bonding plays a role in promoting the electrospinnability of some materials. In this work, the significance of non-covalent interactions in the electrospinnability of aqueous sugar solutions (i.e. mono- and disaccharide) was investigated as a function of carbohydrate concentration. The electrospinnability of concentrated aqueous solutions of glucose, fructose, and sucrose was studied by physicochemical and rheological characterization methods, and by subsequently examining the resulting morphology via scanning electron microscopy. The results on the electrospinning of concentrated saccharide solutions indicated the significance of non-covalent interactions on the electrospinning of these systems. Electrospinnability models based on critical concentration and visco-elasto capillary theories were compared with the experimental results. It is shown that visco-elasto capillary theory has the closest correlation with the experimental data. The electrospinnability of highly concentrated saccharide solutions appears to be directly related to the density and intermolecular bonding capacity of the solution.